SYSTEM OF CORRECTION WORK WITH THE USE OF MANUAL ACTIVITY IN GENERAL SPEECH UNDEVELOPMENT (Conference Zone, 2022)
This article substantiates the relevance of the development of manual activities, reveals the role of this activity in the development of speech, articulatory motor skills, sound pronunciation, etc. The article also briefly describes the results of a diagnostic study of manual activities of preschoolers with general underdevelopment of speech and the effectiveness of a formative experiment in the development of speech through work on manual activities. And the main value of this article is the description of the system of correctional work using manual activities with general underdevelopment of speech.